If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -6x = 19 + 8x Solving 47 + -6x = 19 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 47 + -6x + -8x = 19 + 8x + -8x Combine like terms: -6x + -8x = -14x 47 + -14x = 19 + 8x + -8x Combine like terms: 8x + -8x = 0 47 + -14x = 19 + 0 47 + -14x = 19 Add '-47' to each side of the equation. 47 + -47 + -14x = 19 + -47 Combine like terms: 47 + -47 = 0 0 + -14x = 19 + -47 -14x = 19 + -47 Combine like terms: 19 + -47 = -28 -14x = -28 Divide each side by '-14'. x = 2 Simplifying x = 2
| 7Z-3y=2 | | 6ax-4xb=12 | | N+(4.361)=59.78 | | -41=-3x-5 | | y=5.00+0.25x | | 9(x-1)+x=11 | | 6-9x=6x-9x-6 | | (x^2)+2x+40=(x^2)-x+190 | | 36r^2-1=0 | | 9y-8-6y+7=0 | | -25+55.5+(-29)= | | 6(-3x-3)=5x | | 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 | | -8=6b-14 | | 66.6=3r | | 3e=.75 |